Women empowerment and job performance: Empirical evidence from academia - Segumpan, Reynaldo G.; Mohd Shariff, Roos Niza; Abu Zahari, Joanna Soraya (Penerbit Universiti Utara Malaysia, 2008)
How women compare with men in terms of empowerment and work performance in an academic setting was the main objective of this descriptive-correlation study. The moderating effects of age, work experience, educational qualification, and family role were also examined. Respondents of the study included 263 randomly selected academic staff of a government university; two-thirds of whom were female and one-third were male. Findings showed that women had a "high" empowerment level while men had "moderate" empowerment. Significant differences in empowerment mean scores were noted in terms of age among women, and in terms of educational qualification among men. Educational qualification came out as a significant predictor of empowerment among women, while age and work experience were significant predictors for men. Work performance for both groups was "outstanding," but women had significantly higher mean score than their male counterparts. Likewise, significant differences in work performance were observed as regards educational qualification for both groups, and in addition, with regard to the role in the family for men. Significant predictors of work performance included educational qualification among the women, and age among the men. Empowerment and work performance were not statistically correlated.